Systemic lupus erythematosus during pregnancy is not associated with school performance in offspring – A Danish population-based study. (February 2021) - Knudsen, Signe S; Simard, Julia F; Knudsen, Jakob S; Christensen, Jakob; Laursen, Thomas M; Deleuran, Bent W; Bech, Bodil H
Introduction: Systemic lupus erythematosus (SLE) in pregnancy is considered a risk factor for a range of adverse outcomes in the offspring. Studies have indicated increased risk of neurodevelopmental disorders such as autism spectrum disorders, dyslexia and ADHD. However, the overall long-term cognitive development of children born to women with SLE has scarcely been examined. In this study, we compare test scores from the Danish National School Tests of children born to women SLE with children of the background population. Methods: We included all singleton children born in Denmark between 1995 and 2008, who were listed in the Danish National School Test Register (n=738, 862). Children born to women with SLE were identified through linkage of national healthcare registers. We assessed the children's performance in the national school tests between 2nd and 8th grade, in reading and mathematics. Information on the mothers' redeemed prescriptions in pregnancy was included in stratified analyses. Differences of mean test scores were derived from linear regressions and compared according to maternal SLE status, and predefined categories of medication exposures. Results: In total, 312 (0.04%) children were born to mothers with SLE. There were no differences in performance in neither reading nor mathematics tests between those born to mothers with SLE and children born to mothers without SLE. When stratifying on medication exposures among children whose mothers had SLE, there was a non-significant tendency towards poorer results among those exposed to hydroxychloroquine and/or immunosuppressants (n=31), compared to those not exposed to these medications. A similar tendency was not observed among children whose mothers received hydroxychloroquine for non-SLE reasons (n=1, 235) Conclusion: This study indicates no major harmful effect on the child's neurocognitive development from exposure in utero to SLE, hydroxychloroquine and/or immunosuppressants, as measured by school performance.